Pengembangan Media Pembelajaran “Ultimate” (Multimedia Tematik) Untuk Siswa Kelas IV SD Inpres Padang Raharja - Irwan Adi Prasetiyo; Karlina Wong Lieung; Yonarlianto Tembang (Journal Education Innovation (JEI), 2023)
The Development of "Ultimate" Learning Media (Thematic Multimedia) for fourth grade students at SD Inpres Padang Raharja. This research aims to develop and produce a learning media product, namely interactive learning multimedia that is feasible and practical for learning thematic theme 2 "Always Save Energy" sub-theme 1 "Energy Sources" for fourth grade students at SD Inpres Padang Raharja. This research is a research and development or usually called R&D which refers to the 4D development model with four steps or stages, namely the definition stage, the design stage, the development stage and the dissemination stage. However, the research on the development of "Ultimate" learning media (Thematic Multimedia) intended for grade IV Elementary School which the researcher created could not be continued until the fourth stage, namely dessimination and only reached the development stage. Researcher limited this research to only the development stage due to limited time and cost constraints. By going through these stages th e researcher developed this learning media so that it showed appropriate and practical value for use by fourth grade elementary school students.The results of this research show that the development of "Ultimate" learning media (Thematic Multimedia) is practical and suitable for use. This can be proven from the results of the recapitulation of assessments (validation) by material and media assessors (validators) which show an average score of 4.7 in the "Very Appropriate" category for each assessment (material and media). The results of the practicality test recapitulation by 35 class IV students obtained an average score of 4.56 in the "Very Good" category.